CircHIPK3 Promotes the Tumorigenesis and Development of Gastric Cancer Through miR-637/AKT1 Pathway - Yang, Dejun; Hu, Zunqi; Zhang, Yu; Zhang, Xin; Xu, Jiapeng; Fu, Hongbing; Zhu, Zhenxin; Feng, Dan; Cai, Qingping (Frontiers in Oncology, 2021)
Circular RNA is a kind of RNA with a covalently closed loop, which has a complex ability to modulate genes in the process of tumorigenesis and metastasis. Nevertheless, how circular RNA functions in gastric cancer (GC) remains unclear. The effect of circHIPK3 in vitro was studied here. Quantitative real-time PCR (qRT-PCR) was employed to found that circHIPK3 markedly increased in GC tissues and cell lines. And low expression of circHIPK3 suppressed the GC cells growing and metabolizing. Then the bioinformatics tool predicted the downstream target of circHIPK3, and it was proved by the dual-luciferase report experiment. According to the results of bioinformatics analysis and experimental data, it was clarified that circHIPK3 acted as a sponge of miR-637, releasing its direct target AKT1. The dual-luciferase assay revealed that mir-637 could bind circHIPK3 and AKT1. qRT-PCR data indicated that overexpression circHIPK3 led to the low level of miR-637 and overexpressed miR-637 would reduce AKT1 level. Finally, we demonstrated that the low expression of miR-637 or overexpression of AKT1 could attenuate the anti-proliferative effects of si-circHIPK3. These results suggest that the circHIPK3/miR-637/AKT1 regulatory pathway may be associated with the oncogene and growth of gastric cancer. In short, a new circular RNA circHIPK3 and its function are identified, and the regulatory pathway of circHIPK3/miR-637/AKT1 in the tumorigenesis and development of gastric cancer is discovered.